Armoring and exposure effects on the wave-driven sediment transport. (30th December 2020) - Rafati, Yashar; Hsu, Tian-Jian; Cheng, Zhen; Yu, Xiao; Calantoni, Joseph
Abstract: Coastal sediment transport of graded spherical particles with the material properties of sand was simulated and compared to transport of the uniform-sized spherical particles using a two-phase Eulerian-Lagrangian model. The fluid phase solver was based on SedFoam developed in OpenFOAM and the open-source discrete element method solver LIGGGHTS was used for the particle phase. We validated the model for sheet flow of well-sorted medium sand ( d 50 = 0.28 mm) and mixed sand with bimodal size distribution in velocity-skewed oscillatory flows as well as well-sorted coarse sand ( d 50 = 0.51 mm) in velocity-skewed and acceleration-skewed oscillatory flows. Simulation results of graded particles showed the formation of inverse grading (upward coarsening) in sediment bed under oscillatory flows, suggesting that the effects of armoring and exposure were important in the resulting transport rate. Examining different particle size distributions under onshore velocity-skewed flows, it was found that the largest increase of the net onshore sediment transport rate due to size gradation corresponded to the moderately sorted particle size distribution ( d 90 / d 10 = 3.41), where the coarse fraction ( d > d 50 ) had the maximum contribution to the transport. By analyzing intra-wave sediment transport quantities, the response of size gradation to the flow skewness and asymmetry and velocity intensity was investigated. Model results revealed that the armoring effect (reduction of sediment flux due to inverse grading) was dominant when flow velocity magnitude was lower (wave trough) or the fluid acceleration was higher. On the other hand, when flow velocity magnitude was larger (wave crest), the armoring effect was reduced or the exposure effect (enhancement of sediment flux due to inverse grading) may become more pronounced. Overall, we found that onshore net sediment transport was enhanced up to 30% due to particle size gradation under onshore velocity-skewed oscillatory flows. Conversely, the size gradation reduced the net onshore transport rate up to 35% under onshore acceleration-skewed oscillatory flows. Model results also suggested that the thickness of the active layer (surface layer affected by vertical sorting) in sheet flows can be quantified by the peak erosion depth. The simulation results presented here provide insights into the role of sediment size gradation (armoring and exposure effects) in wave-driven onshore transport which is important for predicting morphological evolution. Highlights Key points: Size gradation influences onshore sediment transport by the inverse vertical grading under the oscillatory flow motions. For coarse sand, armoring effect prevails except for high velocity intensity when exposure effect may become dominant. The transport of graded sediment is dominated by the coarse fraction, which is affected by the degree of size gradation.